Lifestyle medicine: A positive approach to stemming the tide of non-communicable diseases in South Africa - Dave R. Glass (South African Family Practice)
Non-communicable diseases account for most deaths globally and they are the main reason for patient consultations. Conventional medicine focuses on pharmaceutical and surgical interventions to manage these diseases. Most management protocols recognise the foundational role of lifestyle changes, but practical lifestyle medicine interventions need to become part of the medical curriculum and part of each consultation to make an impact. This article presents the rationale for the launch of the South African Lifestyle Medicine Association as an important facilitator of that process.